Cultural Resilience in Print Media: The Case of Djaka Lodang Magazine in Preserving Javanese Language and Local Wisdom - Etik Anjar Fitriarti; Zahrotus Saidah (Yayasan Ilomata, 2026)
Djaka Lodang Magazine, a Javanese-language print medium established in 1971, represents a rare case of cultural resilience amid the dominance of globalized digital media. While existing scholarship on media globalization predominantly emphasizes cultural homogenization, digital disruption, and the decline of local traditions, insufficient attention has been given to how regional-language print media strategically negotiate market pressures while actively sustaining cultural identity. Drawing on the political economy of media and medium theory, this study examines Djaka Lodang as an intrinsic case of local media resilience in preserving the Javanese language and cultural values within a digitized media ecosystem. Using a qualitative intrinsic case study design, data were collected through in-depth interviews, observation, and document analysis, and analyzed thematically to identify patterns in editorial practices, institutional strategies, and cultural narratives. The findings reveal that Djaka Lodang operates not merely as a cultural archive but as an institutionalized mechanism of cultural transmission, sustained through linguistic authenticity, value-driven editorial policies, and community-based networks that selectively engage with, rather than submit to, commercial media logic. This study advances the political economy of media by demonstrating that regional-language print media can function as strategic sites of cultural resistance within contemporary media capitalism. The novelty of this research lies in its theoretical reconceptualization of local print media not as passive victims of digital transformation, but as adaptive actors that reshape media-market relations through cultural capital and community embeddedness. These findings contribute to broader debates on media resilience, cultural sustainability, and the future of minority-language media in the digital era.